Fiber level for laying hens during the growing phase - Ednardo Rodrigues Freitas; Nádia de Melo Braz; Pedro Henrique Watanabe; Carlos Eduardo Braga Cruz; Germano Augusto Jerônimo do Nascimento; Roseane Madeira Bezerra (Ciência e Agrotecnologia, 2014)
Feeding management of laying hens has been focused on the direct influence of nutrient intake on weight gain, especially at growing phase. This study evaluates nutrient digestibility, performance, development of the digestive tract, body composition, and bone quality of two strains of laying hens fed with different levels of neutral detergent fiber (NDF) during the growing phase from the 7th to the 12th week of age. A total of 1,296 birds were distributed in a completely randomized design in a 2 x 3 factorial arrangement (two strains x three levels of NDF) with four replicates of 54 birds per treatment. Semi-heavy (Hy Line Brown) and light-strain (Lohman LSL) pullets were allotted to dietary treatments consisting of 14.50, 16.50, and 18.50% NDF. An interaction between strains and NDF levels was observed only for feed/gain ratio and light-strain pullets had lower performance with 18.50% NDF. The increasing levels of NDF in the diet reduced the coefficients of digestibility of dry matter, nitrogen and gross energy, and the values of metabolizable energy. Higher levels of NDF in the diet increased the relative weight of liver and intestines and reduced gizzard weight. It was also observed differences between bone quality and composition of the femur and tibia of light and semi-heavy hens. The increase in NDF level in ration for growing phase laying hens above 14.50% decreases the nutrient digestibility and the metabolizable energy of the diet; however, it does not affect the carcass composition, bone quality, feed intake, and weight gain, although it may impair feed conversion of light-strain pullets.